PENGARUH MODAL DAN TINGKAT UPAH TERHADAP NILAI PRODUKSI SERTA PENYERAPAN TENAGA KERJA PADA INDUSTRI KERAJINAN KAYU DI KECAMATAN JAMBI TIMUR - Miftahul Janah; Agustina mutia; Muhammad Subhan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine and analyze the influence of capital and wage levels on production value and employment in the wood craft industry in East Jambi sub-district. This research uses a quantitative approach and the data analysis method used is multiple linear regression analysis. The sample used in this research was 79 wood craft business actors in East Jambi sub-district. The results of the t test for the variable influence of capital (X1) on production value (Y1) obtained a significant value of 0.000 < 0.05 and a value of tcount > ttable, namely 6.894 > 2.039. The results of the t test for the variable influence of capital (X2) on labor absorption (Y2) obtained a significant value of 0.000 < 0.05 and a tcount > ttable value of 7.294 > 2.039. The results of the t test for the wage level variable (X2) on production value (Y1) obtained a significant value of 0.000 < 0.05 and a tcount > ttable value of 6.498 > 2.039. The results of the t test for the wage level variable (X2) on the value of labor absorption (Y2) obtained a significant value of 0.000 < 0.05 and a tcount > ttable value of 6.863 > 2.039. Variables influence capital (X1) and wage level (X2) on production value (Y1). The sign value is 0.000 < 0.05 and the fcount>ftable value is 32.961 > 3.29, so Ho is rejected and Ha is accepted and the Adjusted R Square (coefficient of determination) value is 0.680 or 68%. The variable influence of capital (X1) and wage level (X2) on labor absorption (Y2). The sign value is 0.000 < 0.05 and the fcount>ftable value is 38.177 > 3.29, so Ho is rejected and Ha is accepted and the Adjusted R Square (coefficient of determination) value is 0.711 or 71.1%.